ANALISIS PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA WANITA DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DITINJAU DARI HUKUM ISLAM - Lily Handayani (Kafa`ah: Journal of Gender Studies, 2020)
This writing aimed to find out how the forms of legal protection for women workers are stipulated in Law No. 13 of 2003 concerning employment as viewed from an Islamic law perspective. To answer the problems in this study, the authors conducted formative research with a comparative legal study specification. The research method used is library research. The results showed that the legal protection provided by law in the aspects of working time, workplace, leave, menstruation, pregnancy, breastfeeding, and work safety is not balanced with the biological tendency of women that could be painful, and even tend not to make women productive. At the same time, the law does not pay attention to the tendency of today's society that has a higher crime rate so that it is dangerous for women to work at night or in places where they cannot bring their mahram (a member of one’s family). The lack of clarity in attitudes and procedures for legal protection for women workers, according to Islamic law, is not proportional to the risks that will be received by families because they work outside the home beyond their time for children and families.